Post-Emergence Weed Control of Strip-Planted Wheat by Herbicides (Bangladesh Agronomy Journal, 2020)
Transformation of a wheat field from conventionally heavy tillage to stripplanting is beneficial considering soil health improvement and savings in cultivation cost. Therefore, an experiment was conducted at the experimental field of On-Farm Research Division, Bangladesh Agricultural Research Institute, Gazipur during Rabi season of 2017-18 and 2018-19 to evaluate some available post-emergence herbicides for managing weeds in strip-planted wheat var. BARI Gom-30 and to find out the most effective post-emergence herbicide and its suitable rate for controlling weeds under strip tillage system. Three postemergence herbicides (ethoxysulfuron, carfentrazone-ethyl plus isoproturon and carfentrazone-ethyl) were tested at their label rate and double of the label rate and their performance were compared with two times manual weeded control treatment. The study revealed that application of ethoxysulfuron at label rate and double of the label rate was effective for grass weed control, but not for broadleaf weeds. Application of carfentrazone-ethyl plus isoproturon both at label rate and double of the label rate was effective to control all types of weeds. Moreover, the highest grain and straw yields were recorded from label rate application of carfentrazone-ethyl plus isoproturon and its double rate application was also offered similar results in case of grain and straw yields. However; considering undetermined herbicide residual issue and having adverse effect on wheat leaves and finally on yield, the study discourages double of the label rate application of carfentrazone-ethyl plus isoproturon for managing weeds in wheat under strip tillage system.Bangladesh Agron. J. 2020, 23(1): 91-99